Deep Packet Inspection in Linux Kernel Firewall - Bhadade, Vaibhav (My University, 2009)
Deep Packet Inspection technology capable of tracking Internet communications in real time, monitoring the content, and deciding which messages or applications will get through the fastest. There are some Deep Packet Inspection solution available in the market, but each of these have some limitation in one or other aspect. This thesis work discuss Linux based network security concepts, infrastructure, tools and applications and leverages these to build a new user space Application Protocol Interface (API) for Deep Packet Inspection which will provide a consistent, standard and highly exible packet control solution for implementing firewalls.
Keywords: Deep Packet Inspection; DPI